SISTEM INFORMASI PEMBELIAN DAN PENJUALAN OBAT APOTEK KEMIRI SEHAT - , HAMID DAROJAT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
All this time Apotek Kemiri Sehat handle drug inventory management, sales transactions, purchase of medicines, and preparing reports or manually is still not computerized. Difficulties faced when reguler note that if employee have to monitor the availability of the drug, when the drug monitoring has expired, how to record the purchase of drugs (drug entry), recording sales of medicines (drugs out), and collect transactions that numerous reports of certain period. This problem will certainly affect the data processing and preparing reports. Other problem in Apotek Kemiri Sehat is take a long time to monitor the inventory of existing drugs, no reminder drugs were reminded when it expired, and take long time to making reports having to reopen the existing data so that the work becomes less effective. Based on the above circumstances, then a Drugstore Inventory Information System Kemiri Sehat built to handle processing availability of drug, warn when the drug is expired, the purchase of drugs, sale and make recap or report transactions under a certain period. This information system is built using the CodeIgniter framework, MySQL database and javascript framework jQuery for Drugstore. This information systems produce the output of each reporting purchase and sale.